Identification of SNPs in ATP1A1 Gene and their Association with Heat Tolerance in Sahiwal and Karan Fries (Bos taurus × Bos indicus) cattle under tropical climatic condition - Das, Ramendra; Gupta, Ishwar Dayal; Verma, Archana; Chaudhari, Mahesh Vishwas; Sailo, Lalrengpuii; Singh, Sohanvir (Indian Journal of Dairy Science, 2018)
Heat stress produces oxidative stress and affects plasma electrolyte balance. Thermal stress significantly changes in most important transmembrane carrier Na+, K+-ATPase enzyme activity. This enzyme is responsible for establishing electrochemical gradient of Na+ and K+ ions across the plasma membrane. Thereby, represents as a plausible candidate for heat tolerance traits. So, in the study, α1 chain of Na+, K+-ATPase enzyme encoding ATP1A1 gene was targeted to identify single nucleotide polymorphisms (SNPs) by comparative sequencing and also to analyze their association with thermo-tolerance trait viz. respiration rate (RR), rectal temperature (RT) and heat tolerance coefficient (HTC) in three different seasons of the year in Sahiwal and Karan Fries cows. In the study it was observed that, Sahiwal cows are less sensitive and better able to regulate thermoregulatory mechanism in response to high environmental temperature than Karan Fries cows, which may be due to their long time adaptation with tropical climates. Polymorphism of ATP1A1 gene, evaluated by comparative sequencing revealed four SNPs, viz.T27008097A, C27008016T, G27005015A and C27007790A, three SNPs were observed in intron 17 and one SNP observed in exon 18 in both the breeds. It was observed that Sahiwal cows with genotype AA showed significantly (P≤ 0.01) lower HTC than TT and TA genotypes. While, in Karan Fries cows, individuals with genotype TA showed significantly (P≤ 0.01) lower RT than TT genotype. The study inferred that individuals with genotype AA and TA at locus T27008097A improved heat tolerance in Sahiwal and Karan Fries respectively.